Staphylococcal meningitis therapy with linezolid in a young infant: efficacy, CSF levels and side effects - Cinzia Auriti; Fiammetta Piersigilli; Iliana Bersani; Sara Cairoli; Paolina Giuseppina Amante; Daniela Longo; Bianca Maria Goffredo (BMC, 2020)
Abstract Background Linezolid is a synthetic antibiotic which is active against most Gram-positive bacteria, especially on Staphylococcus aureus. Its administration can be required when the infection is due to staphylococcus strains, which are resistant to vancomycin. Although mostly well tolerated, some mild to moderate side effects have been reported. Case presentation This case report describes an infant with multiloculated hydrocephalus, staphylococcal meningitis and prolonged linezolid therapy, in which we observed the association between linezolid administration and a lengthened QTc interval at the electrocardiogram (ECG). To rule out toxic levels during the therapy, plasma and cerebro-spinal fluid concentrations of linezolid were measured and reported. Conclusions Although generally well tolerated in neonates and infants, linezolid prolonged administration seems be able to cause QTc interval prolongation. Therefore, its administration in such patients should be limited to cases of bacterial resistance to other antibiotics. In addition to well-known close monitoring of the platelet level, we suggest serial ECG controls before and during linezolid administration. In the case we report, linezolid plasma concentrations resulted within the therapeutic range during therapy, while cerebrospinal fluid (CSF) concentrations appeared lower than those considered effective.